1987
DOI: 10.1111/j.1748-5827.1987.tb01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light biomicroscopic observations on the pre‐corneal tear film. 1. The normal tear film of the dog

Abstract: Polarized light biomicroscopy was used to examine the normal pre‐corneal tear film in 25 dogs. Blink rates were also determined. The normal range of surface morphology of the canine tear film was established. Three categories of surface patterning of the lipid layer of the tear film were identified. These were: (a) a wave‐like pattern, (b) a pattern of irregular islets, and (c) a pattern resembling the polished surface of granite. All three patterns may occur in the same eye. The inter‐blink thickness of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…These studies confirmed that nocturnal animals blink much less frequently than diurnally active animals, blinking frequency being one-tenth lower in nocturnal versus diurnal mammals [13] and birds [35]. Carrington et al [36] reported that the mean ± SD blink rate in dogs is 14.5 ± 5.63 bpm, and approximately 66% of all blinks were incomplete. Note that interindividual differences are quite large in dogs [36], but much smaller in birds [35].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…These studies confirmed that nocturnal animals blink much less frequently than diurnally active animals, blinking frequency being one-tenth lower in nocturnal versus diurnal mammals [13] and birds [35]. Carrington et al [36] reported that the mean ± SD blink rate in dogs is 14.5 ± 5.63 bpm, and approximately 66% of all blinks were incomplete. Note that interindividual differences are quite large in dogs [36], but much smaller in birds [35].…”
Section: Introductionmentioning
confidence: 64%
“…One series of studies investigated the dopamine hypothesis of blinking in animals [27]–[33]. Another series directly measured the blink rates in animals, including cows [34], birds [35], dogs [36], guinea pigs [37], rabbits [37], [38], and 31 mammalian species [13]. These studies confirmed that nocturnal animals blink much less frequently than diurnally active animals, blinking frequency being one-tenth lower in nocturnal versus diurnal mammals [13] and birds [35].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While this may be true in many cases, mucins are also essential to the stability and spreading of the tear film because they contribute to the surface energy of the ocular surface, optimise the surface tension of the aqueous phase, and reduce the overall surface tension of the film through interaction with surface lipids (Holly and Lemp, 1977 ;Carrington et al, 1987aCarrington et al, , 1987bTiffany, Winter and Bliss, 1989). In addition, their non-Newtonian rheological behaviour (Bron, 1985) makes them ideal lubricants during blinking.…”
Section: -4835\98\120709j10 $3000\0mentioning
confidence: 99%
“…Transposition of the parotid duct is the surgical therapy of choice for treatment for keratoconjunctivitis sicca (KCS) cases that are refractory to medical therapy. Keratoconjunctivitis sicca is primarily a deficiency in the aqueous tear layer of the precorneal tear film, which may be the result of congenital, infectious, immune‐mediated, drug‐induced, iatrogenic, or neuropathic conditions with immune‐mediated being the most common cause 1–9 . Deficiency of tear components can lead to desiccation and inflammation of the conjunctiva and cornea, most often manifested by mucopurulent discharge 10 .…”
Section: Introductionmentioning
confidence: 99%